Uji Potensi Antioksidan Kumis Kucing (Orthosiphon aristatus) dengan Pendekatan In Vitro dan In Silico - Dian Novita W; Silvy Amalia Falyani (Jurnal Kesehatan Islam : Islamic Health Journal, 2021)
Abstract: Orthosiphon aristatus is a potential herb as a source of antioxidants. It is known from previous research, that the active compounds O.aristatus include eupatorin, rosmarinic acid and sinensetin. The study of the potential approach of active compounds extracts O.aristatus with the in vitro methods DPPH (1,1-Difenil-2-Pikrilhidrazil) and in silico using the help of pyrex autodock vina software, with the help of visualization using biovia discovery studio and pymol. Results obtained from in vitro tests using DPPH showed the presence of antioxidant activity with yellow spotting markers against a purple background. Studies in silico show that O.aristatus extract is potentially an antioxidant compound, this is demonstrated through the presence of ligand bonds with glutathione peroksidase (GPX) receptors namely van der Waals bonds, hydrogen bonds and several other bonds.